1991
DOI: 10.1099/0022-1317-72-6-1343
|View full text |Cite
|
Sign up to set email alerts
|

Use of human papillomavirus type 11 virions in an ELISA to detect specific antibodies in humans with condylomata acuminata

Abstract: Human papillomavirus types 6 and 11 (HPV-6 and HPV-11) are the major aetiological agents of condylomata acuminata. Serological studies of this disease have been difficult to perform and interpret because native, type-specific antigens have not been available. In particular, since these viruses have not been propagated in vitro and sufficient quantities of virions are not present in lesions, virus particles have been difficult to obtain. In the present study, we used HPV-11 particles, obtained from human tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…Another potential explanation for the low sensitivity of the HPV-11-based assays is that they are too HPV type-specific. However, HPV-11 whole virion immunoassays are able to detect specific, presumably cross-reactive, antibodies in the sera of patients with condyloma acuminatum or recurrent respiratory papillomatosis who are infected with HPV-6, the other major causal agent of these diseases (Bonnez et al, 1991(Bonnez et al, , 1992a. Therefore, the poor sensitivity of the present arrays cannot be attributed exclusively to narrow typespecificity of the antigen.…”
Section: Short Communicationmentioning
confidence: 78%
See 3 more Smart Citations
“…Another potential explanation for the low sensitivity of the HPV-11-based assays is that they are too HPV type-specific. However, HPV-11 whole virion immunoassays are able to detect specific, presumably cross-reactive, antibodies in the sera of patients with condyloma acuminatum or recurrent respiratory papillomatosis who are infected with HPV-6, the other major causal agent of these diseases (Bonnez et al, 1991(Bonnez et al, , 1992a. Therefore, the poor sensitivity of the present arrays cannot be attributed exclusively to narrow typespecificity of the antigen.…”
Section: Short Communicationmentioning
confidence: 78%
“…The reported sensitivity of currently available HPV-11 virion-based or VLP-based immunoassays is approximately 50% (Bonnez et al, 1991(Bonnez et al, , 1992aCarter et al, 1993; and the present study). There are several possible explanations for such a relatively low sensitivity.…”
Section: Short Communicationmentioning
confidence: 98%
See 2 more Smart Citations
“…Strike et al (1990) and Bonnez et al (1990) have found that Western blots using HPV-6b capsid antigen fusion proteins can not discriminate serologically between condylomata acuminata patients and normal controls. However, an ELISA-based method using whole particles of the closely related HPV-11 is able to do so (Bonnez et al, 1991). The use of immobilized bacterial fusion protein antigens might restrict assay sensitivity by not identifying antibodies targeted to conformational epitopes.…”
Section: Introductionmentioning
confidence: 99%